Hb H Disease Caused by Multiple Mutations in the Polyadenylation Signal Site and − −SEA/αα. (4th May 2017) - Zhang, Qiang; Fan, Xin; Xu, Mingli; Zhang, Yijia; Xu, Huiling; Wen, Xiaojun; Zhou, Wanjun
Abstract: Thalassemia is the most common monogenic disease, with the highest incidence in Guangxi Zhuang Autonomous Region, People's Republic of China (PRC). The blood test result was not consistent with α-globin gene testing in one of the patients during daily screening. It was confirmed that there were multiple mutations at the α2-globin gene polyadenylation (polyA) signal site: HBA2 : c.*64(T>C), HBA2 : c.*68(A>C), HBA2 : c.*71(G>A), HBA2 : c.*74(C>A), HBA2 : c.*82(G>A), HBA2 : c.*92(A>G) and HBA2 : c.*98(T>C) and compound − − SEA /αα by sequencing of the HBA1 and HBA2 genes of the proband and core family members. After that, we found a further two cases of unrelated patients with this type of mutation. The mutation is not an accidental phenomenon, and likely to occur with a considerable incidence in Guangxi Zhuang Autonomous Region, PRC. We analyzed the hematological manifestations of this type of thalassemia and showed that it was a Hb H (β4) disease caused by rare mutations. We suggest that it is essential to pay attention to this mutation during future clinical diagnoses and genetic counseling of patients.